PREDICTIVE ROLE OF HANDS IN STATURE ESTIMATION IN TRIBAL POPULATION OF UDAIPUR IN RAJASTHAN - Taneja, Charu; Jain, L.K (Journal of Forensic Medicine and Toxicology, 2015)
Background: Estimation of stature plays an outstanding role in personal identification. It has a significant importance in forensic anthropometry. Objective: The present study is an attempt to evaluate a possible correlation between stature of an individual and hand length and hand breadth in tribal female population of Udaipur. Material and Methods: The present study was conducted on 200 tribal Females in age group (years) of 18-32. All the measurements were done by using standard anthropometric instruments and standard anthropometric techniques. Results: There was a positive but low correlation between height and various hand parameters. With increase in height there is increase in the hand parameters but with less relationship. For statistical analysis SPSS (Version 17 )was used. Conclusion: The present study has provided regression equations for various hand parameters hand length and hand breadth.
Keywords: Stature; Hand length; Hand breadth; Regression equation